Bonding Performance and Evaluation of Basalt Fiber Asphalt Macadam Seal - Enmao Quan; Yangsen Cao; Hongke Xu (Advances in Civil Engineering)
To broaden the application of the basalt fiber in the preventive maintenance of asphalt pavement, this study investigated the bonding performance and evaluated the comprehensive performance of the basalt fiber asphalt macadam seal. Firstly, different types of basalt fiber asphalt macadam seal were prepared. The influences of content and length of the basalt fiber and dosage of emulsified asphalt on the bonding performance of the asphalt macadam seal were analyzed and compared. Next, by using the efficacy coefficient method, comprehensive performance considering both mechanical and economic characteristics of the basalt fiber asphalt macadam seal was evaluated. After that, reasonable content of each material was determined. Finally, the strengthening mechanism of the fiber on the bonding performance of macadam seals was revealed from a microscopic view. The results showed that compared with the ordinary asphalt macadam seal, the loss aggregate rate of the basalt fiber asphalt macadam seal was 11.0–30.5% lower, and the pull-out strength, shear strength, and torsional shear strength were 11.7–16.3%, 9.7–22.4%, and 4.2–20.6% higher, respectively. Considering the bonding performance and economic benefits, the optimal amount of emulsified asphalt and basalt fiber was 1.6 kg/m2 and 70 g/m2, respectively. Basalt fiber increased the cohesion of the asphalt material and improved the bonding performance of asphalt macadam seals through formation of the three-dimensional network structure. This study can provide reference to the application of basalt fibers in asphalt pavement maintenance.